2010
DOI: 10.3390/ijms11052010
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Novel Microsatellite Markers in Pomegranate (Punica granatum L.)

Abstract: Pomegranate (Punica granatum L.) has been cultivated from ancient times for its economic, ornamental and medicinal properties globally. Here, we report the isolation and characterization of 12 polymorphic microsatellite markers from a repeat-enriched genomic library of Punica granatum L. The genetic diversity of these loci was assessed in 60 genotypes of Punica granatum L. All loci were variable: the number of polymorphic alleles per locus ranged from two to five (average 2.9). The observed and expected hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 9 publications
7
37
3
1
Order By: Relevance
“…This is due to the superior value of the total number of effective alleles, the effective number of patterns/ assay unit and the average number of polymorphic amplicons /assay unit. This finding agrees with previous studies where SRAPs proved to be high effective tools were compared to other marker systems that used each technique separately in pomegranate germplasm, such as, RAPD (Sarkhosh et al, 2006;Narzary et al, 2009), ISSR (Talebi et al, 2005;Narzary et al, 2010), SSR (KoohiDehkordi et al, 2007;Pirseyedi et al, 2010) and SRAP (Soleimani et al, 2012). Other studies in several plants have also confirmed that SRAP is superior information than other methods, for example, RAPD (Liu et al, 2007), ISSR (LiWang et al, 2008) and SSR .…”
Section: Discussionsupporting
confidence: 82%
“…This is due to the superior value of the total number of effective alleles, the effective number of patterns/ assay unit and the average number of polymorphic amplicons /assay unit. This finding agrees with previous studies where SRAPs proved to be high effective tools were compared to other marker systems that used each technique separately in pomegranate germplasm, such as, RAPD (Sarkhosh et al, 2006;Narzary et al, 2009), ISSR (Talebi et al, 2005;Narzary et al, 2010), SSR (KoohiDehkordi et al, 2007;Pirseyedi et al, 2010) and SRAP (Soleimani et al, 2012). Other studies in several plants have also confirmed that SRAP is superior information than other methods, for example, RAPD (Liu et al, 2007), ISSR (LiWang et al, 2008) and SSR .…”
Section: Discussionsupporting
confidence: 82%
“…The main differences were in the observed and expected heterozygosities and the PIC values, which indicated that the characteristics of the loci were strongly influenced by the diversity and origin of the samples included in the analysis. These previous studies focused on the diversity of accessions from Tunisia (14,16) and Iran (15). However, similar genetic parameters to the present study were reported by Soriano et al (7) for the PGCT primer set.…”
Section: Genetic Characteristics Of Pomegranatecontrasting
confidence: 50%
“…Interestingly, the values of the genetic parameters calculated in this study were not very similar to those from the previous studies of Hasnaoui et al (14), Pirseyedi et al (15) and Ebrahimi et al (16). The main differences were in the observed and expected heterozygosities and the PIC values, which indicated that the characteristics of the loci were strongly influenced by the diversity and origin of the samples included in the analysis.…”
Section: Genetic Characteristics Of Pomegranatecontrasting
confidence: 49%
See 1 more Smart Citation
“…Compared to the main fruit crops, pomegranate has not been given much attention from geneticists, cytogeneticists or molecular biologists. There have been reports on pomegranate cultivar identification and genetic analysis using molecular markers (Talebi-Baddaf et al, 2003;Sarkhosh et al, 2006;Masoud et al, 2008;Ebrahimi et al, 2010;Hasnaoui et al, 2010;Pirseyedi et al, 2010). However, the studies on effective identification of pomegranate cultivar are limited, since they utilized selected statistical techniques known as cluster analysis to study the banding pattern.…”
Section: Introductionmentioning
confidence: 99%